Analysis of economic prosperity index based on big data of electricity - Yujiao LIU; Kunhuang SONG; Xiang WANG (Dianxin kexue)
Prosperity analysis is a statistical analysis method of economic cycle.By using monthly or quarterly data economic statistics sequence,the stage of economic development in periodic fluctuations can be analyzed and judged,which can provide reference for government economic policy decision-making and implementation.Electricity data is the “barometer” of national economy.Based on spatio-temporal electric power data and classical economic prosperity model,X13-ARIMA seasonal adjustment algorithm was firstly introduced in the calculation of electric prosperity index to construct an economic prosperity index based on big data of electric power,which objectively reflected the economic operation status and assists in predicting the economic development trend.The calculation achieves the economic goal from the perspective of electricity and provide reference for government policy making.